2013
DOI: 10.3109/10641963.2013.780072
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systolic Blood Pressure and Pulse Pressure with Carotid Intima Thickness in Elderly Japanese Patients

Abstract: Many studies have demonstrated that increased carotid intima-media thickness (IMT) is related to future cardiovascular events and is influenced by cardiovascular risk factors such as sex, hypertension, diabetes, and hypercholesterolemia. Although aging is a well-known risk factor for an increase in carotid IMT, few studies have investigated which factors influence carotid IMT in the very elderly. In the present study, we investigated the relationship of pulse pressure (PP), blood pressure (BP), and its variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Most of the studies investigated on the relationship between carotid IMT and ambulatory BPV, but the subjects did not classify with age and gender. In Oishi's study [32], they investigated the association between SBPV and carotid IMT in elderly Japanese patients aged 70 years or older. They found that mean SBP was positively related with IMT (r = 0.162, P = 0.012), but not DBP or BPV evaluated with SD and CV indices.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies investigated on the relationship between carotid IMT and ambulatory BPV, but the subjects did not classify with age and gender. In Oishi's study [32], they investigated the association between SBPV and carotid IMT in elderly Japanese patients aged 70 years or older. They found that mean SBP was positively related with IMT (r = 0.162, P = 0.012), but not DBP or BPV evaluated with SD and CV indices.…”
Section: Discussionmentioning
confidence: 99%
“…Зміни інтими-медіа каротидних артерій розглядаються як маркер кардіоваскулярного ризику серцевосудинних ускладнень (Michiel et al, 2014). Доведено асоціацію між товщиною інтіми-медіа сонних артерій і підвищенням артеріального тиску у людей похилого віку та дітей, відповідно (Staboulis, 2012;Oishi et al, 2013). Із цієї позиції, наше дослідження поглиблює вивчення морфофункціональних змін серцевосудинної системи за гіпертонічної хвороби та екстрасистолії (Didyk, 2009;Didyk, 2010) та має зв'язок із вивченням даної проблеми у світі (Chen et al, 2015).…”
Section: вступunclassified